Comparison of Civil Law Regarding The Implementation of Cyber Notary in Countries With Common Law and Civil Law Traditions - Ikhsan Lubis; Tarsisius Murwadji; Mahmul Siregar; Detania Sukarja; Robert Robert; Dedi Harianto; Mariane Magda Ketaren (Magister of Law, Faculty of Law, University of Mataram, 2022)
In the era of modern technology as it is today and even more so in the Covid-19 pandemic, cyber notary is also mentioned as a post that needs to carry out each technical aspect of his/her authority and duties as a notary with the help of technology, especially that is related to the urgency of making a notary deed electronically. Article 16, Paragraph (1), lines C and M of the Law on Notary’s Position (Undang-Undang Jabatan Notaris-UUJN) requires a notary to embed a fingerprint as an attachment to the original deed and read out the deed/agreement in the presence of client attended by at least two (2) witnesses, and after being read, should be signed by the client, witnesses, and a notary. Meanwhile, the Law on Article 5 Paragraph (4) on Information Technology and Electronic Transaction (UU ITE) provides limitations by making exceptions to notary deed is not included in the category of electronic information or document. Therefore the problem concerning the creation of a legally binding relationship (a deed) using electronic means (e-Notary) has not yet received a solid legal basis and has not guaranteed legal certainty, especially regarding the authenticity and existence of the electronic deed. In addition, the research will also explore the practice of implementing the development of the cyber notary concept in the field of civil law in several countries, both those with the Common Law tradition and the Civil Law tradition, many of which have empowered the function and role of a notary in electronic transactions. The utilized research technique is the normative legal research technique by using the approach to legislation and analysis of legal concepts sourced from primary or secondary legal materials. The results indicate that the concept of a cyber notary in creating a deed by electronic means (e-Notary) requires arrangements that provide clear rules regarding the terms or conditions in the framework of making a notary or authentic deed conducted using the concept of a cyber notary. Thus, the notary can carry out professional duties without contradicting the laws and regulations. In addition, the development of the cyber notary concept that comes from the Common Law System tradition in practice has been widely applied and is no exception for the Indonesian state which is included in the tradition of countries that adhere to the Civil Law System as a modern legal state, of course, cannot escape developments outside the law.